Remote sensing of water-related hazards - Zhang, Ke; Hong, Yang; AghaKouchak, Amir (Hoboken, NJ Wiley-American Geophysical Union, 2022)
Applications of remote sensing technology for monitoring and predicting water-related hazards. Water-related hazards such as floods and droughts have serious impacts on society. Their incidence has increased in recent decades, a trend set to continue with ongoing climate change. Adaptation and mitigation measures require accurate detection, monitoring, and forecasting, much of which comes from remote sensing technologies. Remote Sensing of Water-Related Hazards takes an interdisciplinary approach, presenting recent advances in the available data, sensors, models, and indicators developed for monitoring and prediction. Volume highlights include: Progress in remote sensing of precipitation, storms, and tornados Different techniques for flood mapping, forecasting, and early warning Integrated approach for predicting flood and landslide cascading hazards Satellite monitoring of water cycle variation, water scarcity, and drought conditions Multi-indicator and multi-sensor approaches for quantifying drought impacts The American Geophysical Union promotes discovery in Earth and space science for the benefit of humanity. Its publications disseminate scientific knowledge and provide resources for researchers, students, and professionals."--
Includes bibliographical references and index.
Keywords: Hydrological forecasting; Remote sensing